The guide [large type] : a novel - Heller, Peter, 1959- (Random House Large Print, 2021)
"The bestselling author of 'The River' returns with a heart-racing thriller about a young man who, escaping his own grief, is hired by an elite fishing lodge in Colorado where amid the natural beauty of sun-drenched streams and forests he uncovers a plot of shocking menace"--